Over- and Under-Perceiving Social Support from One's Partner and Relationship Quality Over Time. Issue 8 (17th November 2018) - Reifman, Alan; Niehuis, Sylvia
Abstract: Using dyadic data from a national longitudinal survey in Germany ( N = 3, 674 couples), we tested associations between congruence/discrepancy in partners' reports of providing and receiving social support (i.e., whether a recipient reports more or less than the provider) and relationship quality. All participants reported how much social support they provided to, and received from, their partner. Latent Congruence Modeling was used to enhance the reliability of difference scores between one partner's reported provision and the other's reported receipt. In most instances, perceiving more support than one's partner reported giving (over-perception) and extensive support reported jointly by providers and recipients were positively associated with recipients' and providers' relationship quality. Conceptual, methodological, and possible clinical issues are discussed.